Thermoforming Process Simulation Of Stretchable Electronic Circuit - Ismail, Nur Amirah (Universiti Sains Malaysia, 2018)
Thermoforming is a well-known manufacturing process where a polymer sheet is heated to pliable condition at the forming temperature and stretched into a specific shape in a mould and finally trimmed to obtain a usable product. Thermoforming process is used widely in industry because of its cost-effective manufacturing process. The main objective of this project is to study the effect of the thermoforming process and parameter on the thickness distributions of the thermoforming product by using ANSYS Polyflow simulation. ANSYS Polyflow simulation is used to study the overall thermoforming process to save time and reduce the cost used to produce any prototype product. Mould with different shapes which are corner edge (3mm fillet) and sharp edge are used and simulated to obtain the best thickness distribution on the product. Mould with corner edge (3mm fillet) reduced and distributed the stress more evenly on the product. Therefore, the value of the thickness at the inside corner (critical corner) has been reduced. Grid analysis is performed on the thermoforming product with and without printed circuit. The result showed that the substrate elongated more without the printed circuit on it. The deformation of the substrate with printed circuit embedded on it is much lower. However, the substrate is able to well deform with the printed circuit according to the shape of the mould. Larger area stretch ratio is found at the critical corner and lower sidewall. Higher elongation occurred as the depth of draw increased. Therefore, the thickness distributions are reduced and increased the area stretch ratio as the depth of draw increased. In conclusion, the understanding and technique of thermoforming process on the lighting part has been fully developed.